(untitled) (Fiep Bulletin - online, 2015)
Introduction: Thermoregulation has an important role in body homeostasis. Thermal stress can modify the level of activation of cognitive processes responsible for the motor perception and actions, leading to performance reduction. Moreover, dehydration can significantly increase rectum temperature and cardiac heart rate, reducing sweat production, V02max. and the exercise performance, in comparison with conditions of normal hydration. As judo is a sport modality practiced at enclosed environment with heavy and thick clothes, the jodgui, the heat loss can be reduced, compromising the athlete performance, mainly on training programs. Aims: study the effects of hydration in the thermoregulatory mechanisms during the training of judo athletes. Method: the sample consisted of 10 judo athletes with more than five years of practice (average age of 17 years and 18.46% of corporal fat). The athletes appeared for two training days consisted of a habitual judo training, duration of 1 hour and 40 minutes, following four days of regular training and a 48 hours rest. Subjects were divided in two experimental balanced groups, a) hydrated (HJ - the athlete ingested 200 ml of water every 15 minutes during the training) and b) not hydrated (NHJ - the athlete did not ingest water during the training). This study it was approved by the Committee of Ethics in Research of the UNIBH. During both training sections heart rate, tympanic temperature and sweating rate were accessed. The data were analyzed by pared Student "t" test (p<0.05). Results: The following differences between HJ and NHJ were observed: heart rate (155 bpm in NHJ and 147 bpm in HJ) and mean tympanic temperature during training section (36.26ºC in NHJ and 35.99ºC in HJ). Sweating rate was not different between the training section where the athletes ingested water compared in the one water ingestion was not allowed. Conclusion: Hydration during training section affected heart rate and mean tympanic temperature.